Pengalaman dan Pelatihan untuk Meningkatkan Kesiapsiagaan Bencana Perawat Unit Gawat Darurat - Herlin Lidya (FORIKES, 2023)
Disaster conditions have a major impact on health services. A large spike in patients in a short time can cause nurses to be overwhelmed in treating patients, especially disaster victims. Therefore, emergency room nurses as the first line of defense need to have good disaster preparedness, especially triage and appropriate treatment for patients. This study aimed to describe the factors that influence the disaster preparedness of emergency nurses in providing disaster management. This study was a literature review. The electronic databases used in the literature search consisted of ProQuest, ScienceDirect, SAGE Knowledge and Emerald Insight with the keywords